Greening the retail banking industry: Evidence from German bank account consumers - Klein, Sophie Maria Anneke; Polzin, Friedemann (Elsevier Inc., 2025)
While investor behaviour in relation to sustainable finance products has recently received scholarly attention, consumer adoption of these products remains poorly understood. This study investigates the reasoning behind adopting sustainable bank accounts at the household level using a quantitative approach with a nationally representative sample of 1501 consumers in Germany. The most important determinant for adopting these accounts was sustainable finance self-efficacy – in other words, the perceived impact that the consumer can make by using the product. Other significant determinants include the consumers' willingness to pay a premium for the sustainability characteristic. Sustainable values, trust in bank in provider, and financial literacy are less relevant drivers of adoption. The study identified five distinct consumer clusters with different levels of adoption to generate more targeted industry and policy responses due to limited uptake. The results highlight the need for product providers and policymakers to raise awareness of the impact of private finances on sustainability in order to accelerate the adoption of sustainable banking products.
Keywords: Banking market segments; Consumer behaviour; Self-efficacy; Sustainable banking product adoption; Willingness to pay; Finance; Economics and Econometrics; SDG 12 - Responsible Consumption and Production